The Religions Of Oceania. - Swain, Tony (Taylor & Francis Ltd., 1995)
This constitutes the first up-to-date study of the great and changing variety of traditional religions in the regions of Australia, Melanesia, Micronesia and Polynesia, collectively known as Oceania.